Photobiomodulation therapy for the prevention of acute radiation dermatitis in head and neck cancer patients (DERMISHEAD trial). (May 2021) - Robijns, Jolien; Lodewijckx, Joy; Claes, Stefan; Van Bever, Leen; Pannekoeke, Luc; Censabella, Sandrine; Bussé, Lore; Colson, Dora; Kaminski, Iris; Broux, Victoria; Puts, Sofie; Vanmechelen, Sofie; et al.
Highlights: Evaluation of the efficacy of photobiomodulation (PBM) for acute radiodermatitis. First randomised, placebo-controlled trial in head and neck cancer patients. PBM significantly reduces the severity of acute radiodermatitis. Evidence for implementation of PBM in clinical practise is strengthened. Abstract: Background and purpose: The purpose of this study was to investigate the effectiveness of photobiomodulation therapy (PBMT) for the prevention of acute radiation dermatitis (ARD) in head and neck cancer (HNC) patients. Materials and methods: A randomised, placebo-controlled trial (RCT) with 46 HNC patients who underwent radiotherapy (RT) with or without concomitant chemotherapy was set up (DERMISHEAD trial). Patients were randomised to receive PBM or placebo treatments from the first day of RT (2×/week) alongside the institutional skincare. The severity of skin reactions was assessed by the National Cancer Institute-Common Terminology Criteria for Adverse Events version 4.03 (NCI-CTCAE v4.03) and the Radiotherapy-Induced Skin Reaction Assessment Scale (RISRAS). Quality of life (QoL) was evaluated using the Skindex-16 questionnaire. Results: PBMT significantly reduced NCI-CTCAE grade 2–3 ARD with 49% at the end of RT. Conclusion: The results of the first RCT in HNC patients showed that PBMT is an effective method to prevent the development of severe ARD. These results support the implementation of PBM in the clinical oncology – radiotherapy practice.